Eksistensi Penyelesaian Sengketa Masyarakat Hukum Adat dalam Pencegahan Perusakan Kawasan Hutan - Taufik Siregar; Fitri Yanni Dewi Siregar (Universitas Medan Area, 2022)
This study aims to find out that forest management often occurs when conflicts arise between the community and the state regarding land/natural resources. In customary law communities, disputes that have occurred have long been resolved by deliberation and consensus through customary institutions known as customary courts. This study uses normative legal research that is descriptive analytical, with a normative juridical approach, namely an approach based on the main legal materials related to this research. The data analysis in this study was carried out qualitatively. The results of the study indicate that the existence of customary law as a component of legal substance must be given a reasonable place in the development of legal materials in accordance with the socio-cultural diversity of the community. Disputing Indigenous Peoples generally have different customary laws which are strongly adhered to by the community, so that it can make it difficult to resolve disputes that occur. In general, the causes of this case are due to the acquisition of forest areas for plantations, usurpation of customary lands and violations of other prohibitions by plantation companies against customary law